Selective electrochemical reduction of CO2 to formic acid in a gas phase reactor with by-product recirculation. Issue 6 (8th March 2021) - Thijs, Barbara; Rongé, Jan; Martens, Johan A.
Abstract : A reactor concept is proposed where recirculation of by-products such as H2 enhances the product selectivity of electrochemical CO2 reduction to formic acid. Abstract : Recirculation is a chemical engineering concept generally applied to enhance the conversion of reagents. In common applications, by-products are removed together with the desired products and only the unconverted feed is recirculated. In the concept proposed here to enhance the electrochemical reduction of CO2 to formate or formic acid, by-products are recirculated to the reactor together with unconverted CO2 . Initial accumulation of by-products like H2 in the reactor shifts the electrochemical formation potential of these undesired by-products to higher values and favours in this way the formation of formic acid, for which the potential is unaffected. Mathematical simulation of this recirculation process revealed formate selectivity to be substantially improved when by-products are recirculated, even at low pressure. The concept was experimentally validated in an experiment with a membrane electrode assembly reactor. In gas mixtures containing 0.07 MPa of H2 and 0.03 MPa of CO2, the hydrogen selectivity of the electrochemical reduction was decreased by ca. 40% as opposed to pure CO2 . This leads to a significant increase in the formate selectivity and energy efficiency. By-product recirculation to enhance the reaction selectivity may be advantageous to other applications of electrocatalysis suffering from low selectivity of the electrocatalyst.